Which battery-charging technology and insurance contract is preferred in the electric vehicle sharing business?. (June 2019) - Wu, Peng
Abstract: The adoption of electric vehicles (EVs) is emerging in the car-sharing business due to the high potential of reducing operational costs as well as greenhouse gas emissions. In this early stage of the EV-sharing business, it is still unclear which battery-charging technology and insurance contract would be more competitive for EV-sharing operators in the context of future business. We have developed a stylized model with which to analyze the impact of different charging technologies, insurance contracts and other related factors on the EV-sharing operator's profit. The operator's demand is derived from customers' utility of driving under a membership scheme. Various operational costs such as electricity and parking place costs are considered. Different battery-charging technologies and insurance contracts are incorporated into the model and then compared. The results show that membership and driving time are strategic complements, and that the operator's profit is sensitive to policy interventions. Fixed-premium insurance leads to lower prices for the EV-sharing service than per-hour-premium insurance. The per-hour premium fees decrease more significantly than the fixed premium fees as autonomous vehicles reduce accident costs. The conditions for different battery-charging technologies to be price competitive are identified and meaningful policy implications are derived.